An Improved Clarke and Wright Algorithm to Solve the Capacitated Vehicle Routing Problem - Caccetta, L.; Alameen, M.; Abdul-Niby, M. (Engineering, Technology & Applied Science Research, 2013)
This paper proposes an effective hybrid approach that combines domain reduction with the Clarke and Wright algorithm to solve the capacitated vehicle routing problem. The hybrid approach is applied to solve 10 benchmark capacitated vehicle routing problem instances. The dimension of the instances was between 21 to 200 customers. The results show that domain reduction can improve the classical Clarke and Wright algorithm by about 18%. The hybrid approach improves the large instances significantly in comparison with the smaller size instances. This paper will not show the time taken to solve each instance, as the Clarke and Wright algorithm and the hybrid approach took almost the same CPU time.